Influences and Impact of Anxiety and Depression in the Setting of Inflammatory Bowel Disease. Issue 11 (17th May 2018) - Navabi, Seyedehsan; Gorrepati, Venkata Subhash; Yadav, Sanjay; Chintanaboina, Jaykrishna; Maher, Sarah; Demuth, Peter; Stern, Benjamin; Stuart, August; Tinsley, Andrew; Clarke, Kofi; Williams, Emmanuelle D; Coates, Matthew D
Abstract: Background: Individuals with inflammatory bowel disease (IBD) are at increased risk of developing anxiety or depression (A&D). Crohn's disease (CD) and ulcerative colitis (UC) with comorbid A&D are both more challenging to manage. IBD providers need to better understand the causes and impact of A&D in order to improve care for IBD patients. We sought to identify clinical factors that influence development of A&D and healthcare utilization in IBD. Methods: This is a retrospective analysis using an IBD natural history registry from a single tertiary care referral center. Presence of A&D was determined based upon responses to the Hospital Anxiety and Depression Scale. Demographic and clinical factors were abstracted to evaluate for significant associations. Results: Four hundred thirty-two IBD patients (132 UC, 256 CD, and 44 indeterminate colitis) were included in this study. One hundred ninety-two (44.4%) had anxiety or depression or both, and most were female (59.4%, P < 0.05). History of surgery ( P < 0.05), female gender ( P < 0.05), smoking ( P < 0.05), and extra-intestinal manifestations ( P < 0.01) were each independently predictive of A&D. Inflammatory bowel disease patients with A&D more often underwent imaging studies (53.6% vs 36.7%, P < 0.05), visited the ED (30.7% vs 20.8%, P < 0.05), or were hospitalized (31.7% vs 21.7%, P < 0.05). They were also more frequently prescribed corticosteroids (50.5% vs 36.7%, P < 0.01) and biologic medications (62.5% vs 51.3%, P < 0.05). Finally, they were more likely to have had at least 1 "no-show" (29.2% vs 16.7%, P < 0.01) and had a higher mean number of "no-shows" (0.69 +/- 0.1 vs 0.30 +/- 0.1, P < 0.01) over the study period. Discussion: Anxiety and depression are common in the setting of IBD and are strongly associated with surgical history, disease complications (including extra-intestinal manifestations), smoking, and female gender. Inflammatory bowel disease patients with A&D are also more likely to require therapy and to utilize healthcare resources. This study refines our understanding of A&D development and its impact in IBD and provides additional considerations for management in this setting.